Autonomous data driven surveillance and rectification system using in-vehicle sensors for intelligent transportation systems (ITS) - Khalid, Aaqib; Umer, Tariq; Afzal, Muhammad Khalil; Anjum, Sheraz; Sohail, Adnan; Asif, Hafiz Muhammad (Computer networks (Amsterdam, Netherlands : 1999), 2018)
Road safety through vehicular control is the prime interest of research in Vehicular Ad hoc Networks (VANETs). Diagnostic analysis of In-vehicle sensors is one of the core concerns for vehicular safety. There is a number of safety applications promising the features needed in vehicular safety. Therefore, this paper designed, developed, and implemented a solution for diagnostic analysis of In-vehicle sensors with autonomous recovery procedure. An artificial intelligence-based technique is used for monitoring, reporting and autonomous recovering of vehicle sensors. The algorithm used for diagnostic analysis of sensors not only determines the operational state of the sensors but also executes procedure for sensors autonomous recovery. A graphical display depicts the operational state of sensors for driver’s information. Hexadecimal message format is implemented for transmission and reception of sensors data to the central administration unit using Internet Protocol (IP). The simulation results confirm the effectiveness of proposed solution in term of recovery time of faulty sensor.